Pengaruh Lama Waktu Fermentasi Kulit Pisang Siem (Musa x paradiciaca ABB (CV.”Pisang Siem”) terhadap Kadar Alkohol - Jesica Ayu Indraswari; Maryanti Setyaningsih; Susilo Susilo (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2021)
This study aims to determine the effect of long fermentation time banana peel (Musa x paradiciaca ABB (cv. "Pisang Siem”) to the amount of alcohol. This research was conducted at Greenhouse FKIP UHAMKA in August-September 2015. The method used is experimental methods with completely randomized design (CRD). In this research there were 5 treatment each 6 replications. The treatment are P1, P2, P3, P4 and P5 with long fermentation time for 1 day, 3 days, 5 days, 7 days and 9 days. The results showed the level of alcohol in the treatment are 14,85% P1,19,33% P2,24,08% P3,28,23% P4 and17,21% P5.Statistical analysis showed that the treatment effect on parameters of alcohol. The high alcohol measure indicated in the treatment P4 is 28.23%. It can be concluded that the long fermentation time banana peel effect on alcohol measure. The results of the study of the effect of fermentation time on alcohol content showed a difference in the treatment. This may be because the microbes are in the exponential phase. The exponential phase is a phase when microbes experience rapid growth in which the number of cells increases exponentially with time. In the exponential phase, environmental conditions change, as substrates and nutrients are consumed while metabolism is produced.This study aims to determine the effect of long fermentation time banana peel (Musa x paradiciaca ABB (cv. "Pisang Siem”) to the amount of alcohol. This research was conducted at Greenhouse FKIP UHAMKA in August-September 2015. The method used is experimental methods with completely randomized design (CRD). In this research there were 5 treatment each 6 replications. The treatment are P1, P2, P3, P4 and P5 with long fermentation time for 1 day, 3 days, 5 days, 7 days and 9 days. The results showed the level of alcohol in the treatment are 14,85% P1,19,33% P2,24,08% P3,28,23% P4 and17,21% P5.Statistical analysis showed that the treatment effect on parameters of alcohol. The high alcohol measure indicated in the treatment P4 is 28.23%. It can be concluded that the long fermentation time banana peel effect on alcohol measure. The results of the study of the effect of fermentation time on alcohol content showed a difference in the treatment. This may be because the microbes are in the exponential phase. The exponential phase is a phase when microbes experience rapid growth in which the number of cells increases exponentially with time. In the exponential phase, environmental conditions change, as substrates and nutrients are consumed while metabolism is produced.